Aplikasi Pupuk Urea Terhadap Pertumbuhan Dan Hasil Tanaman Kangkung Darat (Ipomoea reptans Poir) - Tatuk Tojibatus Saadah; Mahrus Ali; Megawati Citra Alam (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta, 2023)
The application of fertilization sourced from inorganic fertilizers is still not much done. Moreover, to determine the efficiency (profitable) and effectiveness (effectiveness) of the use of these fertilizers on vegetable crops, including kale. For this reason, it is necessary to study further the use of inorganic fertilizers. The aim of the study was to determine the application of Urea fertilizer on the growth and yield of water spinach (Ipomoea reptans Poir). This research method used a randomized block design (RBD) consisting of seven (7) doses of urea fertilizer with three (3) replicates and two (2) sample plants. The placement of the urea fertilizer dose treatment in the experimental plots was carried out randomly. The results of the research on the treatment of giving a dose of 150 kg/ha of urea fertilizer resulted in maximum growth and yield of land spinach plants.